Analysis of Environmental Conditions and Its Effects Towards The Success of Student Learning in Senior High School in Subdistrict Kampar Timur - Respita Febri; Gimin Gimin; Sumarno Sumarno (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
This study aims to analyze the environmental conditions and their influence directly and indirectly on the success of student learning in high schools in Kampar Timur Subdistrict. The data used consists of primary and secondary data. The data is collected using questionnaires and documents. The study population was 567 high school students in Kampar Timur Subdistrict with a sample of 235 students taken by proportional random sampling. The analytical method used is path analysis. The results of the analysis show that family environment and community environment variables directly influence the school environment by 13.54% and 4.58%. Then the variable school environment, family environment and community environment affect the success of learning. The direct effect of the school environment on learning success is 24.70%. While the total direct and indirect influence of the family environment is 12.82% and the community environment is 4.84%.